Photocatalytic Degradation Of Phenol And 2,4-Dichlorophenol Using Rare Earth-Doped ZnO Hierarchical Micro/Nanospheres Under Fluorescent Light And Sunlight Irradiation - Sin, Jin Chung (2014)

(untitled)
Widespread concerns continue to be raised about the impacts of exposure to chemical compounds with endocrine disrupting activities. To date, the percolation of endocrine disrupting chemical (EDC) effluent into the aquatic system remains an intricate challenge abroad the nations. Heterogeneous photocatalysis using ZnO hierarchical architectures has recently been emerged as an efficient and feasible technology for the purification of polluted water. In this study, ZnO hierarchical micro/nanospheres doped with rare earth ion (RE/ZnO, RE ion = Ce, Eu and Nd) were synthesized using a chemical precipitation method for the photocatalytic degradation of two EDCs, namely phenol and 2,4-dichlorophenol (2,4-DCP) under fluorescent light and sunlight irradiation. Kebimbangan berterusan ditambahkan terhadap kesan pendedahan kepada bahan kimia dengan aktiviti pengganggu endokrin. Setakat ini, pengasingan effluen bahan kimia pengganggu endokrin ke dalam sistem akuatik masih adalah satu cabaran yang rumit bagi banyak negara. Fotopemangkinan menggunakan hierarki ZnO baru-baru in ditampilkan sebagai teknologi yang cekap dan boleh dipraktikkan untuk rawatan air tercemar. Dalam kajian ini, hierarki ZnO berbentuk sfera mikro/nano terdop dengan ion nadir bumi (RE/ZnO, ion RE = Ce, Eu and Nd) telah disintesis dengan kaedah pemendakan kimia untuk fotodegradasi dua jenis bahan kimia pengganggu endokrin iaitu fenol dan 2,4-diklorofenol (2,4-DCP) di bawah penyinaran lampu pendarfluor dan cahaya matahari.